Facilitators and barriers to the assimilation of function-specific executives into senior management roles. Issue 4 (10th August 2015) - Bennett, Roger
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the factors that might contribute to the ease with which marketing executives in UK charities who have been promoted to senior general management positions adjust to the occupancy of these roles. Design/methodology/approach – In total, 37 individuals with functional marketing backgrounds currently holding top general management positions in large fundraising charities were interviewed using a frame-worked occupational autobiographic narrative approach. The research was informed by aspects of newcomer adjustment theory, notably uncertainty reduction theory. Findings – Social and personal considerations were much more important determinants of the ease of assimilation into top management positions in charities than were technical job-related matters. Role ambiguity constituted the main barrier to smooth adjustment. Mentoring, planned induction programmes, the nature of a person's past work experience and the individual's social status critically affected how readily a marketer fitted into a top management role. Disparate sets of factors influenced different elements of managerial newcomer adjustment (role clarity, self-efficacy, and social acceptance). Research limitations/implications – As the participants in the study needed to satisfy certain narrowly defined criteria and to work in a single sector (large fundraising charities) the sample was necessarily small. It was not possible to explore the effects on operational performance of varying degrees of ease of newcomer adjustment. Practical implications – Individuals promoted to top management posts in charities should try psychologically to break with the past and should not be afraid of projecting a strong functional professional identity to their new peers. These recommendations can be expected to apply to organisations in general which, like large charities, need senior management mentoring and induction programmes to assist recently promoted individuals from function-specific backgrounds; job descriptions for top management posts that are clear and embody realistic expectations; and "shadowing" and training activities for newly appointed senior managers with function-specific backgrounds. Originality/value – The study is the first to apply newcomer adjustment theory to the assimilation of functional managers into more senior general management. It examines a broader range of potential variables affecting managerial newcomer adjustment than has previously been considered. Relevant issues are examined in the context of an important sector: fundraising charities.